2010
DOI: 10.1038/ijo.2010.231
|View full text |Cite
|
Sign up to set email alerts
|

Central regulation of feeding behavior during social isolation of rat: evidence for the role of endogenous CART system

Abstract: Objective: Although hyperphagia and body weight gain are well-recognized consequences of social isolation, the underlying mechanisms are not understood. The aim of this work is to test the possibility that the endogenous cocaine-and amphetamineregulated transcript peptide (CART) may be involved in the process. Design: Socially isolated rats were screened for increase in food intake and body weight, and the modifications of these parameters by CART were evaluated. Furthermore, isolated animals were re-socialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
6
29
0
Order By: Relevance
“…Icv administration of 0.5 or 1 g of CART produced significant reduction in food intake in normal rats [14,26] as also observed in the present study. However, in binged rats, twice the dose of CART was required to produce similar degree of reduction in HFSPD intake.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Icv administration of 0.5 or 1 g of CART produced significant reduction in food intake in normal rats [14,26] as also observed in the present study. However, in binged rats, twice the dose of CART was required to produce similar degree of reduction in HFSPD intake.…”
Section: Discussionsupporting
confidence: 90%
“…Omission of the primary antibody and replacement with BSA produced no synaptophysin immunoreaction. In preadsorption controls, application of diluted antibody pre-incubated with CART at 10 −5 M for 24-h, completely blocked the CART-immunoreaction [26].…”
Section: Immunohistochemistrymentioning
confidence: 95%
See 1 more Smart Citation
“…CART protein is encoded by the CARTPT gene, which functions in feeding, reward, stress and pain transmissions [152,153]. Similar to POMC, CART also downregulates food intake and body weight [154,155]; a previous study revealed that CART has an effect on neuronal activities (including the hypothalamic VMH and PVN), which are involved in the neuroplasticity of hypothalamic feeding circuits [156].…”
Section: The Role Of Pomc and Cart In Sga-induced Weight Gainmentioning
confidence: 99%
“…This is consistent with literature demonstrating that social isolation can modify feeding habit without changing body weight. In rats, 6 but not 3 weeks of isolation increased bodyweight though both increased weekly food intake (Nakhate, Kokare, Singru, & Subhedar, 2011;Perez et al, 1997). In mice, neither 2 nor 8 weeks of isolation changed body weight in adult mice despite altering feeding (Sun et al, 2014;Yamada et al, 2015).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 87%